The basic principles of DNA damage detection by the alkaline comet assay - Živković, Lada; Topalović, Dijana; Djelić, Ninoslav; Popović, Petar; Marković, Milica; Gunjić, Ilija; Spremo-Potparević, Biljana (Archives of Pharmacy, 2024)
The Comet assay is a highly sensitive and rapid method for detecting DNA damage at the level of individual cells. It measures single-stranded and double-stranded DNA breaks, alkali-labile, incomplete excision repair and cross-linking sites. A major advantage of the Comet assay is its applicability to both proliferating and non-proliferating cells, and it can be performed on all types of eukaryotic cells. The basic principle of the alkaline Comet assay is to lyse the biological membranes to release proteins bound to the DNA, followed by a short-term electrophoresis at a pH above 13. Through this process, the DNA fragments migrate and form a comet-like shape, which is visualized by staining with a DNA-binding fluorescent dye. The extent of electrophoretic migration is proportional to the amount of DNA damage. Key advantages of the Comet assay include sensitivity - the assay can detect low levels of DNA damage, versatility – it can be used with a small amount of test substance, speed – results are usually available within 24 to 48 hours, and broad applicability – the method is suitable for numerous purposes, including molecular epidemiology, occupational exposure studies, environmental biomonitoring, antigenotoxicity assessments and clinical research. Overall, the Comet assay provides valuable data for a range of scientific and clinical fields, making it a versatile and powerful tool for assessing DNA damage.
Keywords: DNA damage; comet assay; eukaryotic cells